A Route to Indoles via Modified Fischer Indole Intermediates from Sulfonanilides and Ketene Dithioacetal Monoxides. Issue 10 (1st September 2020) - Kinoshita, Jun; Baralle, Alexandre; Yoshida, Akira; Yanagi, Tomoyuki; Nogi, Keisuke; Yorimitsu, Hideki
Abstract: An S−N variant of the N−N‐based Fischer indole synthesis has been developed. Treatment of sulfonanilides and ketene dithioacetal monoxides with a powerful acid anhydride provides N ‐sulfonyl‐2‐methylsulfanylindoles. The initial interrupted Pummerer reaction would yield the key S−N‐tethered precursor in situ that then undergoes [3, 3] sigmatropic rearrangement, after which the endgame to the indole ring follows the Fischer manner. Abstract : The modern Pummerer chemistry has allowed the development of a new route to indoles from sulfonanilides and ketene dithioacetal monoxides. Upon activation of the sulfoxide with acid anhydride, an interrupted Pummerer reaction with sulfonanilide yielded an S−N variant of the N−N‐based intermediate in the Fischer indole synthesis. The S−N‐tethered intermediate follows a Fischer‐like pathway to the corresponding N ‐sufonyl‐2‐methylsulfanylindole of synthetic use.